A Study on the Personality Traits that Define Investor Behaviour in Karnataka - Khatun, Rinki (Journal of Global Economy, Business and Finance, 2025)
Investment in stocks or mutual funds is associated with the socioeconomic condition of people. Openness is found as the most important characteristic that influences the stock market performance of people in Karnataka. In addition to this, investors have proper awareness regarding the market dynamics. Good investors must have the capability of risk tolerance in order to analyse the correct stocks. Along with that, understanding as well as accepting volatility is another component of having investor behaviour. These people are decisive and thereby good investors take proper decisions in order to gain a high amount of profitability from the market. In this study, a secondary qualitative type of data has been collected by the researcher. Articles published in the last 5 years are collected by the researcher in order to successfully fulfill the aim of the study. Along with that, the researcher used Google Scholar for determining the accurate data regarding personality traits in Karnataka. The findings of this study confirmed that working women in Karnataka with higher income levels take moderate risk while investing in mutual funds. On the other hand, male in Karnataka with proper awareness regarding the market and openness characteristics tend to invest more in different sticks. On the other hand, neuroticism has the opposite impact on the investment decisions of individual people in Karnataka.